Verification and testing RKHS series summation method for modelling radio electronic devices - Chumachenko, S. V.; Chugurov, I. N.; Chugurova, V. V. (EWDTW, 2005)
Reproducing Kernel Hilbert Space (RKHS) for Series Summation that allows analytically obtaining alternative representations for series in the finite form is developed. To increase efficiency of solving of computational tasks there are used mathematical co-processors, which implement most efficient ways of computing equations, integrals, differential coefficients, ets. It is obvious that after discovering of new methods of increasing computation accuracy and decreasing computation time it is necessary to re-implement mathematical coprocessors or use new generation of IP-cores in PLD, Gate Array, ASIC designs. The method of reduction of computation of certain types of series to exact function that is widely used during calculation of parameters of high radio frequency devices was presented in [1-4]. This method decrease computation time of such tasks in tens and hundred times and its inaccuracy is equals to zero. The purpose of the investigation is verification and testing Series Summation Method in RKHS for modelling radio electronic devices.
Keywords: Hilbert space; reproducing kernel; RKHS; series summation method